Microbiological substantiation of the effectiveness of quercitin and its combination with ethylmethylhydroxypyridine succinate in the complex treatment of odontogenic phlegmon and maxillofacial abscesses - Lokes, Kateryna; Kiptilyi, Anatolii; Skikevych, Margaryta; Steblovskyi, Dmytro; Lychman, Vitaliy; Bilokon, Serhii; Avetikov, David (Frontiers in Oral Health, 2024)
Odontogenic infections can become life-threatening. The aim of the study was to determine the effectiveness of quercitin and its combination with ethylmethylhydroxypyridine succinate in the complex treatment of odontogenic infections by assessing the microbial population of the infection site. Materials and methods. The cross-sectional study included 75 patients. Purulent exudate was collected from the infection site. The number of colony-forming units was counted using the standard plate method. Results. The microbiological examination of purulent exudate obtained from the patients revealed the general prevalence of Gram-positive cocci. On the seventh day of treatment, the total number of microorganisms in the purulent exudate of patients in group I, whose treatment included a combination of the standard protocol with quercitin, significantly decreased compared to the first day of the same group. The results of treatment of patients in group II, which included the standard protocol in combination with quercitin and 2-ethyl-6-methyl-3-hydroxypyridine succinate, demonstrate a significant decrease in the total number of bacteria in the infection focus on the fifth day of treatment compared to this indicator of the group at the beginning of the study. Conclusions. When quercitin was used as part of complex treatment, the total treatment period was reduced by 1.4 days. However, the combined use of quercitin and ethylmethylhydroxypyridine succinate against the background of standard treatment of patients with odontogenic infection contributed to a reduction in hospital stay by 2 days.